Consumer Motivations for Adopting Omnichannel Retailing: A Safety-Driven Perspective in the Context of COVID-19 - Liu, Feng; Fang, Mingjie; Cai, Lanhui; Su, Miao; Wang, Xueqin (Frontiers in Public Health, 2022)
This study aims to understand the influence of COVID-19 on consumers' fears and self-protection motivations. Furthermore, the study seeks to understand the effects of these fears and motivations on consumers' intentions to use omnichannel retailing. A modified theoretical model is proposed by integrating protection motivation theory (PMT) and extending the extended parallel process model (E-EPPM). A total of 398 valid questionnaires are collected and used for further structural equation modeling analysis. The results suggest that the perceived severity, perceived vulnerability, and health anxiety positively impact perceived fears surrounding COVID-19. Furthermore, it is found that perceived fear, self-efficacy, and response efficacy will affect the protection motivation of consumers and ultimately contribute to their behavioral intention to use omnichannel retailing. The findings theoretically enrich the research on COVID-19, PMT, and E-EPPM and empirically provide managerial implications for omnichannel retail service providers.